The new encrusting microproblematicum Circumpodium enigmaticum and its attachment trace Circumpodichnus serialis from the Middle Jurassic of Normandy (France) - M. Wisshak; L. Hüne (Fossil Record, 2019)
A single specimen of an enigmatic new attachment etching, together with an unknown calcareous encruster partly preserved in situ, has been identified on a belemnite rostrum from the Marnes de Dives Formation (Callovian, Middle Jurassic) of the Falaises des Vaches Noires in Normandy, France. The trace fossil, here established as the new ichnotaxon Circumpodichnus serialis igen. et isp. n., is a uniserial arrangement of very shallow depressions, oval to fusiform in outline, with peripheral pouches and central pits. The trace maker has a morphology unlike any other known calcareous epibiont, fossil or recent, and is consequently described as the new microproblematicum Circumpodium enigmaticum gen. et sp. n. Its calcitic skeleton is composed of a chain of segments with perforate basal and lateral walls, anchored to the attachment trace in the substratum by vertical protrusions in the centre and feet-like protrusions in the periphery. The hypothetical upper wall of the segments was either organic-walled and has decayed or it was calcitic and has been abraded. Based on morphological criteria and the capacity to bioerode, C. enigmaticum can best be compared to encrusting bryozoans and foraminiferans. Candidate bryozoans are aberrant arachnidiid ctenostomes, early cheilostomes, or stomatoporid cyclostomes. Among the foraminiferans, webbinellid or ramulinid polymorphinids are closest in their characters. In addition, tintinnid or folliculinid ciliophorans are considered as an alternative interpretation, and similarities to the Palaeozoic microproblematicum Allonema are discussed.